ANALISIS RASIO LEVERAGE/ SOLVABILITAS (LEVERAGE RATIO) SEBAGAI ALAT PENGAMBILAN KEPUTUSAN PADA PERUM PERUMNAS REGIONAL VII - Tamsil Tamsil (AkMen JURNAL ILMIAH, 2014)
The study aims to determine Ratio Levarage / Solvency Housing Regional Housing VII for 5 (five) years of 2006 s / d 2010. While the analysis tools used in this study is an analysis of the financial ratios to see which indicators could cause the company's performance has increased or decreased. The results showed that the solvency ratio for 5 (five) years from 2006 s / d 2010 for the ratio of debt compared to total assets indicates that the company can guarantee all the debts of the total assets owned by the company. As for the ratio of debt to equity percentage menujukkkan positive, it is a portrait that companies can bear the entire debt of the capital owned.